Adipose-derived exosomes impairs endothelial transient receptor potential vanilloid 4 channels and elevates blood pressure in abdominal obesity. (14th October 2021) - Wan, J; Liu, S; Yang, Y; Wang, D; Ran, F; Dai, X; Zhou, P; Wang, P
Abstract: Aim: Large epidemiological studies have found that abdominal obesity is a strong risk factor for hypertension. Impaired endothelium-dependent vasodilation is a hallmark of obesity-induced hypertension. Adipose-derived exosomes can regulate distant tissues as novel adipokines, providing a new mechanism for cell-cell interactions. However, the effects of adipose-derived exosomes on obesity-induced hypertension are unknown. Methods: We extracted three adipose-derived exosomes, including high-fat diet (HFD) mouse serum exosome, adipose tissue exosome, and adipose-derived stem cell exosome, and further explored their effects on endothelium-dependent vasodilation in vivo and in vitro. Results: Impairment of endothelial transient receptor potential vanilloid 4 (TRPV4) channel activity and vasodilation were observed in the arteries from abdominal obesity patients. Ca2+ influx through TRPV4 channels at myoendothelial projections to smooth muscle cells decreases resting blood pressure in nonobese mice, a response that is diminished in HFD mice. Administration of three exosomes elevated blood pressure by promoting artery endothelial barrier permeability, impairing the expression of adherens junctions, and aggravating inflammatory response in vivo and in vitro, accompanied by TRPV4/Ca2+ pathway inhibition. Conclusions: Impairment of endothelial TRPV4 channels contributes to obesity-induced hypertension and imply that HFD-induced obesity plays a role in blood pressure by aggravating the artery endothelial barrier injury and inflammatory response via adipose-derived exosomes, at least partially, through inhibiting the TRPV4/Ca2+ pathway. Funding Acknowledgement: Type of funding sources: None. Main funding source(s): This research was supported by grants from the National Natural Science Foundation of China (81970262) (P.J.W.), Innovation Team Project Department of Education of Sichuan Province (18TD0030) (PJW), Central Funds Guiding the Local Science and Technology Development of Sichuan Province (2020ZYD036, P.W.), and grants from the Scientific Research Fund of Chengdu Medical College (CYZYB20-07) (J.W.).